Effect of nano-bubble water on high solid anaerobic digestion of pig manure: Focus on digestion stability, methanogenesis performance and related mechanisms. (November 2020) - Fan, Yujie; Lei, Zhongfang; Yang, Xiaojing; Kobayashi, Motoyoshi; Adachi, Yasuhisa; Zhang, Zhenya; Shimizu, Kazuya
Highlights: Nanobubble water addition alleviated the inhibition form the accumulation of VFAs. Methanogenesis performance was enhanced in high solids anaerobic digestion process. Digestion stability was improved under nanobubble water addition. The consumption of soluble proteins/carbohydrates was promoted by nanobubble water. Abstract: In this study, high solid anaerobic digestion of pig manure (PM) under nano-bubble water (NBW) addition was investigated with focus on digestion stability, methanogenesis performance and related mechanisms. Volatile fatty acids (VFAs) inhibition occurred when total solids (TS) was about 8% without NBW addition, which was alleviated with improved digestion stability under NBW addition, facilitating the process of high solids anaerobic digestion (HSAD). The cumulative CH4 yield, on the other hand, was 201–230 mL/g-VS in the NBW reactors at TS of 3–6%, about 20.3–25.0% higher than the control reactors. At the same time, with higher water mobility and zeta potential, NBW was found to promote the consumption of soluble proteins/carbohydrates during the above AD process.